Analisis Kelayakan Bisnis Yoghurt Susu Sapi: Model Berkelanjutan untuk Pengusaha Pemula di Indonesia - Hariyani, Nunuk; Farida, Siti; Purwanti, Gettik Andri; Ferdian, Muh. Agus (JURNAL GREEN HOUSE, 2025)
The cow's milk yoghurt industry in Indonesia shows great potential, but there are still many challenges related to product quality and business feasibility, especially for start-up entrepreneurs. Previous research has focused more on technical aspects, without considering business aspects that are relevant in the Indonesian context. This study definitively explores the influence of production factors on yoghurt quality and business viability. The study's primary objectives were clear: to assess the impact of starter type and incubation time on yoghurt quality and to analyze the business viability of cow's milk yoghurt production for novice entrepreneurs. The approach used was an experimental design with a quasi-experiment test. We collected data through experiments using two types of starter—Greek and Plain—with incubation times varying from 18 to 24 hours. Product quality was evaluated using pH and organoleptic tests, and business feasibility was analyzed using financial analysis. The study focused on two key factors: yoghurt quality and business feasibility. Greek starter with an incubation time of 24 hours produced more favorable yoghurt. The financial analysis unequivocally confirmed the yoghurt business's profitability, with a high ROI and a low break-even point. These findings are vital for the development of the yoghurt industry in Indonesia and provide clear direction for future research on production factors and consumer preferences.